ANALYSIS OF IN VITRO DISINTEGRATION AND DISSOLUTION EFFECT OF CUCURBITA MAXIMA STARCH IN LOSARTAN FDT - VARGHESE, NINA; KOMALA, M. (International Journal of Applied Pharmaceutics, 2022)
Objective: In this work, Curcurbita maxima was used as a superdisintegrant in the preparation of fast dissolving tablets containing Losartan. A Losartan is readily ionized in the presence of an acidic pH, resulting in decreased absorption via the GIT. Superdisintegrant can be used to solve this problem. Methods: Losartan fast-dissolving tablets were made using the direct compression method and two distinct superdisintegrants, derived starch and Curcurbita maxima mucilage, in various quantities. Eleven formulations with varied concentrations of superdisintegrants were created to determine their efficacy and critical concentration levels. For each formulation, several pre-compression and post-compression assessment parameters were used. Results: The disintegration time of the FDT (F1-F4) prepared with derived starch ranges from 4.28±1.02 min to 8.20±1.02 min, while the disintegration time of the FDT (F5-F8) prepared with Cucurbita maxima starch ranges from 1.02±0.02 min to 5.02±1.02 min. The remaining three formulations, F9-F11, have a disintegration time of more than 10 min. In comparison to other formulations, FDT containing Curcurbita maxima mucilage demonstrated improved organoleptic qualities, as well as outstanding in vitro disintegration and dissolution drug release. Conclusion: It was determined that a lower concentration of Cucurbita maxima starch (10 mg) was the optimal concentration level for the Losartan FDT formulation.